OCT angiography in optic disc drusen: comparison with structural and functional parameters. Issue 8 (19th November 2019) - Engelke, Hendrik; Shajari, Mehdi; Riedel, Julian; Mohr, Niklas; Priglinger, Siegfried G; Mackert, Marc J
Abstract : Background: Optic disc drusen (ODD) can cause retinal nerve fibre layer (RNFL) defects with progressive visual field (VF) loss. Microvascular changes are discussed as a cause. We measured the vessel density (VD) of the optic disc in ODD using optical coherence tomography angiography and compared it with a normal population. Another intent was to determine the sensitivity and correlations in comparison with functional (VF) and structural parameters (RNFL, minimum rim width (MRW), ganglion cell complex (GCC)). Methods: We analysed the VD of 25 patients with ODD and an age-matched control population including 25 healthy participants using AngioVue (Optovue, Fremont, CA, USA). We obtained data about RNFL, GCC, Bruch's membrane opening MRW (Spectralis HRA & OCT; Heidelberg Engineering, Germany) and VF (standard automated perimetry; SITA 24-2). Low image quality and pathologies interfering with the diagnostics were excluded. Parametric data were analysed using the t-test and non-parametric values using the Mann-Whitney U test. Linear regression analysis was used to determine correlations using the Bravais-Pearson test. Results: The VD was significantly reduced in the ODD group especially the peripapillary capillary VD (n=45 vs 50 eyes; mean 43.15% vs 51.70%). Peripapillary RNFL thickness correlated with the VD significantly (r=0.902 (n=44), 0.901 (n=44), 0.866 (n=45)). The RNFL analysis showed a reduction in ODD, especially the superior hemisphere (mean 107 µm, 129 µm; 49 vs 50 eyes). The GCC was significantly lower in the ODD group (n=38 vs 40; mean 87 µm vs 98 µm). Positive correlation between the VD and the GCC was significant (n=37, r=0.532). There is a significant negative correlation (n=19; r=−0.726) between the VD and the pattern standard deviation (PSD). Conclusion: This study reveals significant peripapillary microvascular changes in patients with ODD correlating with the RNFL and GCC reduction. There is a negative correlation between the PSD and the VD.